Comparison of the in vitro Effect of Chemical and Herbal Mouthwashes on Candida albicans - Talebi, Somayeh (Jundishapur J Microbiol, 2014)
BACKGROUND: During the recent decades research has focused to find scientific evidence for the effects of herbal medicines. Researchers are interested in herbal remedies for medication and aim to substitute herbal material instead of chemical formula with limited side effects for human being. OBJECTIVES: The aim of the current study was to compare the in vitro effect of herbal and chemical mouthwashes against Candida albicans. MATERIALS AND METHODS: In this research, we used a standard strain of C. albicans, PTCC 5027. The suspension was made by a fresh culture of C. albicans (24 hours) and the optical density (turbidity equating to a McFarland standard of 0.5) was read at 530 nm. The C. albicans suspension was cultured on Sabouraud dextrose agar plate. Next, two wells were filled with mouthwashes and after incubation at 30ºC for 24 hours, the inhibition zone was measured. Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of mouthwashes were determined. Data were analyzed using the SPSS software, independent T-tests and one-sided variance analysis (ANOVA-one way). RESULTS: Based on these findings on agar diffusion with (P = 0.764), MIC and MFC tests (P = 0.879), there were no significant differences between the antifungal effect of herbal and chemical mouthwashes. CONCLUSIONS: This study showed that, chemical mouthwashes acted better than herbal mouthwashes and among different chemical mouthwashes, Oral B was most effective.